Kids make music! : clapping & tapping from Bach to rock - Hart, Avery; Mantell, Paul.; Braren, Loretta Trezzo (Charlotte, Vt. : Williamson Pub., 1993)
Presents a variety of activities based on music, including singing and dancing, improvisation, and making homemade instruments.
"A Williamson kids can! book."
Includes index.
Keywords: Games with music; Exercise music; Music; Games with music